2005
DOI: 10.1055/s-2004-830355
|View full text |Cite
|
Sign up to set email alerts
|

Acute Epididymitis in Children: A 4-Year Retrospective Study

Abstract: AE seems to be more common than acute TT. Urinalysis and urine culture should be performed for all children with AE. High resolution ultrasound with an experienced investigator is able to exclude TT reliably so that routine surgical exploration is seldom necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 14 publications
4
32
1
Order By: Relevance
“…If the history and physical examination are sufficiently alarming, then scrotal exploration is used even if "normal flow" was observed on the ultrasound study [1]. Haecker et al based on their own results and the experience of a majority of other authors propose a reasonable diagnostic and therapeutic algorithm for acute scrotum [8]. The present study confirms the importance of color Doppler ultrasound as a diagnostic tool for the exclusion of testicular torsion among children with acute scrotum.…”
Section: Discussionsupporting
confidence: 89%
“…If the history and physical examination are sufficiently alarming, then scrotal exploration is used even if "normal flow" was observed on the ultrasound study [1]. Haecker et al based on their own results and the experience of a majority of other authors propose a reasonable diagnostic and therapeutic algorithm for acute scrotum [8]. The present study confirms the importance of color Doppler ultrasound as a diagnostic tool for the exclusion of testicular torsion among children with acute scrotum.…”
Section: Discussionsupporting
confidence: 89%
“…[2,5,11] Urine cultures were inconclusive in the majority of the patients in the current study and showed infection with Pseudomonas in 3 patients, and this clinical data is similar to the literature. [12,13] However, the urine culture-proven infection rate of 51.6% has also been reported in children with epididymitis. [14] The incidence of underlying urogenital anomaly in our patients with EO was 22.7% (5 of 22) and is consistent with previous reports.…”
Section: Resultsmentioning
confidence: 99%
“…Acute epididymo-orchitis or epididymitis is the most common cause of an acute scrotum in adolescent boys and the most frequent non-surgical cause of the acute scrotum (14,15). These are unusual in early neonatal life.…”
Section: Discussionmentioning
confidence: 97%